[Immigrations to Anatolia, related public health problems and healthcare services in the beginning of the Twentieth Century]. [Yirminci yüzyilin başlarinda Anadolu'ya göçler, oluşan halk saǧliǧi sorunlari ve sunulan saǧlik hizmetleri.] - (:unkn) unknown (My University, 2006)
Anatolia, one of the most important crossroads between two continents, has witnessed so many immigrations throughout the history. It is a place where different civilizations and cultures met and transformed each other by interaction. History of important immigrations to Anatolia during the reign of the Ottoman Empire goes back to 1683. Also, the period between the end of 19th century and the beginning of 20th century was the time of wars, immigrations, and death and birth of nations. The Ottoman Empire had joined the several wars as well, and the new Republic of Turkey was established after it collapsed. In this study, we investigated the two large scale immigrations to Anatolia between Balkan Wars and the first years of Republic, and tried to compile our knowledge about the public health problems and the healthcare services provided.